Fasilitas Pemberdayaan Masyarakat Berbasis Pertanian Lahan Kering di Badung: dengan Pendekatan Perilaku - I Putu Andi Wira Adnyana; Anak Agung Gede Raka Gunawarman; Ni Putu Ratih Pradnyaswari Anasta Putri (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Community empowerment is a process of activities that are carried out intentionally in an effort to increase the ability of the community to involve the community as empowerers and empowered communities. Good empowerment needs to design facilities in accordance with the empowerment activities carried out. One of them is empowerment based on dry land agriculture in South Kuta District. This facility is developed by considering the approach to user behavior. The purpose of the research is to find the right behavioral approach model for empowerment activities with data collection methods by literature studies and field observations. The results obtained show that each space that is formed can accommodate the behavior of its users so as to maximize the use of space and make users comfortable using the space.